2003
DOI: 10.2460/javma.2003.223.1130
|View full text |Cite
|
Sign up to set email alerts
|

Taurine deficiency in Newfoundlands fed commercially available complete and balanced diets

Abstract: Results indicate a high prevalence of taurine deficiency among an environmentally and genetically related cohort of Newfoundlands fed apparently complete and balanced diets. Blood taurine concentrations indicative of taurine deficiency in Newfoundlands may be substantially less than concentrations indicative of a deficiency in cats.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
37
0
2

Year Published

2005
2005
2024
2024

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 64 publications
(46 citation statements)
references
References 36 publications
5
37
0
2
Order By: Relevance
“…None of the dogs in the CVD group had plasma taurine concentrations that would be considered deficient (ie, ,40 nmol/mL) at any time point. 14,15 However, the fact that taurine concentrations decreased from visit 2 to visit 3 suggests that higher taurine content would be desirable in the cardiac diet.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…None of the dogs in the CVD group had plasma taurine concentrations that would be considered deficient (ie, ,40 nmol/mL) at any time point. 14,15 However, the fact that taurine concentrations decreased from visit 2 to visit 3 suggests that higher taurine content would be desirable in the cardiac diet.…”
Section: Discussionmentioning
confidence: 99%
“…1,[5][6][7][8][9][10][11][12][13][14][15] Dietary intake of nutrients in dogs with cardiac disease can be extremely variable. As an example, one study showed a variation of sodium intake for dogs with cardiac disease to be 14-384 mg/ 100 kcal and protein intake to be 2.3-18.8 g/100 kcal.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…85 Dietary factors that are important considerations for taurine status in dogs include low dietary protein, feeding a primary protein source that contains low or less available SAAs, and the use of rice bran. 84 However, neither of these studies was controlled and both included dogs fed a variety of commercial foods. Soybean protein is low in SAAs and the formation of bile acid complexes may further contribute to fecal loss of taurine.…”
Section: Taurinementioning
confidence: 99%
“…In 1987, an association between clinical cases of DCM in cats and taurine levels in pet food was found; taurine supplementation completely reverses the condition (see Chapter 12, pp. 39,40,41,[44][45][46][47][48] Any factor that results in increased colonic bacteria populations leads to increased taurine loss in the feces and thus an increased dietary requirement for this nutrient. 9 Commercial pet food companies that increased the concentration of taurine have further supplemented taurine levels in feline diets, and thus there has been a dramatic reduction in cases of DCM in cats.…”
Section: Specific Nutritional Modifications In Managing Cardiovasculamentioning
confidence: 99%